EXPANDING GLOBAL ACCESS TO EMERGENCY CONTRACEPTION A COLLABORATIVE APPROACH TO MEETING WOMEN'S NEEDS - CONSORTIUM FOR EMERGENCY CONTRACEPTION; Foster, A. M.; Wynn, L. L. (GRAPHIC DESIGN BY ELIZABETH SANDERS, 2000)
"Globally, more than one fourth of all pregnancies are unintended. Emergency contraception can be used after sex to reduce the risk of pregnancy. But despite their safety and efficacy, emergency contraceptive pills (ECPs) have sparked controversy worldwide. In examining the journey of ECPs in fourteen countries, this volume explores the ways that a global reproductive health technology both acquires local cultural meaning and encounters similar challenges everywhere it is introduced worldwide. This book's portraits of activism and opposition highlight the range of social, cultural, religious, and political contexts that shape the interpretation of new medical technologies"--
Machine generated contents note: -- PART I: Setting the context * The birth of a global reproductive health technology: An introduction to the journey of emergency contraception--L. L. Wynn & A. M. Foster * Emergency contraception: Hopes & realities--J. Trussell * PART II: Country case studies * United States: Activism, sexual archetypes, and the politicization of science--L. L. Wynn * Canada: Competing frames of access and authority--J. N. Erdman * Jamaica: A success story in moving to nonprescription status--D. Chin-Quee * Mexico: Expanding access through partnerships and persistence--R. Schiavon & E. Westley_ * Chile: One step forward, one step back--V. Schiappacasse & S. Di;az * Britain: Contradictory messages about sexual responsibility--A. Furedi * France: A pioneer in the switch to nonprescription status--C. Moreau & E. Gainer * Tunisia: A global leader in reproductive health and rights--A. M. Foster * Lebanon: Can introduction be too quiet?--F. El-Kak * Morocco: A personal account of the introduction saga--S. Harti * Nigeria: Creating demand and increasing availability--D. A. Lang, J. Keesbury & A. S. Karlyn * Australia: Organized physician opposition to nonprescription status--H. Calabretto * Bangladesh: A model for national family planning program integration--S. M. I. Hossain & M. E. Khan * The Thailand-Burma border: Addressing needs in long-term conflict settings--C. Sietstra * PART III:_ Conclusion * The future of emergency contraception: Where are we now and where are we going?--E. Westley.
Keywords: Emergency contraceptives; Birth control; Human reproductive technology; SOCIAL SCIENCE / Abortion & Birth Control; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / International Relations / General